The Implementation of The Religion Rights for Transgender In Indonesia - Budhi, Ratih Andani Setyo (UI Scholars Hub, 2023)
The rights to conduct religious practice are undoubtedly essential for all human beings, including transgender people. However, in practice, they often found obstacles in implementing their fundamental rights to pray to God. The main objectives of this paper are to understand the statutory laws applicable in Indonesia regarding the rights of the religion of the Indonesians for transgenders, and how is the actual implementation by the government in fulfilling the rights, as well as examining case experienced by the transgenders who live in Pondok Pesantren Waria (Female Transgender Madrasa) Al- Fatah Yogyakarta. The Author was using a combination of library and internet research complemented by primary legal sources such as legislation and case law in discussing the research materials. Through in-depth discussion in this article, the Author supports the notion that Indonesia must enhance its commitment to protecting all kinds of genders, particularly in the issue of religion through the existence of a particular law for religion. The Author also encourages the government to draft a specific law related to religion. Finally, this research concludes that at this moment transgender has certainly limited opportunities to perform their religions in the public sphere due to insufficient respect given by society.